Case report: Fulminant extraneural metastasis of glioblastoma through venous sinus - Kim, Yeong Jin; Ahn, Kang Hee; Lee, Kyung-Hwa; Moon, Kyung-Sub (Frontiers in Oncology, 2022)
Background Extraneural metastasis (ENM) of glioblastoma are rare. However, as patient overall survival improves, the incidence of ENM has gradually increased. Although several risk factors have been proposed, venous sinus invasion was regarded as a very exceptional route for ENM. Case description We report a 60-year-old man with glioblastoma in the temporal lobe, invading the transverse and sigmoid venous sinus. After gross total tumor resection, the patient received the standard chemoradiation therapy. Systemic evaluation for persistent shoulder and back pain revealed widespread metastasis to lymph nodes and multiple bones 9 months after surgery. Despite spine radiation therapy, the patient became paraplegic and died 1 year after surgery. Conclusions Venous sinus invasion should be kept in mind by physicians, as a risk factor for glioblastoma ENM. Systemic evaluation of these patients with extracranial symptoms should be performed without hesitation.